Performance of turmeric (Curcuma longa L.) varieties in lower Pulney hills of Tamil Nadu, India - MADHUSOODANAN, D V PATIL, K M KURUVILLA, K J (Journal of Spices and Aromatic Crops, 1995)
Eight turmeric (Curcuma longa) varieties were evaluated under rainfed conditions for two crop seasons at lower Pulney hills, Tamil Nadu, India. The varieties differed among themselves with regard to yield and growth characters such as plant height, number of tillers per plant, leaves per tiller, leaflength and breadth and curing percentage. Suvarna (PCT-8) had maximum number of tillers per plant but was inferior to others in relation to other growth traits. The highest yield (t/ha - fresh rhizomes) was recorded in BSR-l (20.88), followed by Suvarna (19.32) and Suroma (19.04).